The Inca's two bodies: the prison condition in Latin America - Ariza, Libardo José (Punishment in Latin America, 2025)
In this chapter, we show how physical violence is a central part of the prison experience in Latin America. Such a violence is perceived both a legally admitted and forbidden practice. In this sense, corporal punishment appears not as an imperfection, but rather an ordinary element of punitive power in the region. This strange existence of corporal punishment as permitted and forbidden violence ends up by legitimizing the punishment of the inmates in their physical body and their existence as a subject of law. This juxtaposition places prisoners’ bodies “betwixt and between” the natural world and the normative world of punishment. Thus, the life of prisoners is protected by law. Their indemnity is recognized, and their fundamental rights are guaranteed. However, at the same time, their lives are expendable.